2019
DOI: 10.1371/journal.pntd.0007033
|View full text |Cite
|
Sign up to set email alerts
|

Association study between CCR2-CCR5 genes polymorphisms and chronic Chagas heart disease in Wichi and in admixed populations from Argentina

Abstract: Several studies have proposed different genetic markers of susceptibility to develop chronic Chagas cardiomyopathy (CCC). Many genes may be involved, each one making a small contribution. For this reason, an appropriate approach for this problematic is to study a large number of single nucleotide polymorphisms (SNPs) in individuals sharing a genetic background. Our aim was to analyze two CCR2 and seven CCR5 SNPs and their association to CCC in Argentina. A case-control study was carried out in 480 T. cruzi ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
0
16
3
Order By: Relevance
“…Our global analysis of the rs1799988 polymorphism did not find differences between the analyzed groups, but in the analysis of the subgroup of countries formed after Spanish colonization [10,26,28], the codominance model showed an association between the homozygous T/T genotype and the cardiac form of CD, while the recessiveness model associated the same T/T genotype with the cardiac form. Unlike our findings, Nogueira et al [25] identified an increased C/C genotype and C allele in the cardiac group (CCC) compared to the moderate group.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Our global analysis of the rs1799988 polymorphism did not find differences between the analyzed groups, but in the analysis of the subgroup of countries formed after Spanish colonization [10,26,28], the codominance model showed an association between the homozygous T/T genotype and the cardiac form of CD, while the recessiveness model associated the same T/T genotype with the cardiac form. Unlike our findings, Nogueira et al [25] identified an increased C/C genotype and C allele in the cardiac group (CCC) compared to the moderate group.…”
Section: Discussioncontrasting
confidence: 61%
“…Machuca and others [28] have already established a relationship between the G allele and some degree of CCC severity, supporting our results. The rs1800024 SNP indicated the T allele as a risk factor for cardiomyopathy in CD, also previously suggested by Juiz and coauthors [26], although different from the results of Machuca et al [28], which related the allele with the severity of the disease.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The upregulation of CCR5 in CD8 + T-cells from T. cruziinfected mice has been associated with tissue damage (81,82). Genetic variants of CCR5 have been associated with human Chagas disease (83), and high CCR5 expression by leukocytes has also been associated with severe CCC (27,84). The analysis of CCR5 expression frequency showed a high frequency of CD4 + , CD8 + and TCRgamma-delta+ DN T-cells expressing this molecule in CCC compared to IDC.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility to the development of CCC is a matter of ongoing investigation of immunity genes to identify possible individual and population-based predisposition. Table 4.3 [83][84][85][86][87][88][89][90][91] lists the genes and related variants investigated to date in CD. Although some association studies tested positive, no genetic test is currently performed in the diagnostic work-up of CD.…”
Section: Chagas Disease and Genetic Predispositionmentioning
confidence: 99%